(3CHhGH GdLfGf hHTGFQ GdQVhGfs - (3Bd NOGe, GdHGgdj, GdYaeGhj, GdfLaj, NVQ Hf TdGd Hf NWGH, J (B1255 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3ef GdeYdhe Cf eG QZH GdTGQY ajg HGdKhGH ef GdCYeGd hGdBOGH (B.. (3hbO PcQ YdeGDfG hCSdGafG WGH eKhGge LedI efgG aj cJHge GdabgjI GdaQYjI hCdahG (B...s
(3BNQgG (B:s
... (3hfMh Pdc aj SGFQ Wjf GdbHhQ GdeTQaI ef GdeYUhejf hbO jMed YdHg eG hQO aj ZjQ Wjf GdMSjf GdefJaY HWjfg cd ef (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1/671s
(3GdPQjYI (B1- 58 (367)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis